Pemanfaatan Program Canva Creator Dalam Menumbuhkan Brand Awareness Studio Provo - Pratama, Aditya; Retnasary, Maya (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Studio Provo is a creative studio that provides several digital products and services in the field of graphic design. This study aims to find out how the Canva Creator program is utilized in building Studio Provo brand awareness. The type of research used is descriptive with a qualitative approach. The researcher carried out the object of study and held direct interactions with Studio Provo informants and made observations on the Canva Creator Page and Social Media Studio Provo. Technical data analysis is carried out by obtaining an understanding of the research focus, then a conclusion will be drawn in the form of a general understanding based on reality. The findings obtained in this study indicate that the Canva Creator Program and Social Media provide a separate role for Studio Provo in maximizing its benefits as a medium of communication between Studio Provo and its audience and consumers, as well as a medium for building brand awareness.